2019
DOI: 10.1016/j.jcmgh.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Ductal Deletion of Hnf1b Disrupts Exocrine Homeostasis, Leads to Pancreatitis, and Facilitates Tumorigenesis

Abstract: This study shows how Hnf1b inactivation in pancreatic ductal cells leads to chronic pancreatitis, neoplasia, and potentiates pancreatic intraepithelial neoplasia formation. This shows a cause of pancreatitis and identifies Hnf1b as a potential tumor suppressor for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 82 publications
0
40
0
Order By: Relevance
“…74 Inactivation of HNF1B by Cre-Sox9 recombination was found to cause chronic pancreatitis with dilation of ducts, acinar-to-ductal metaplasia and lipomatosis. 75 Inactivated HNF1B in mouse ductal cells was seen to decrease the expression of Prox1, Pkhd1, Spp1 and Cys1, which play an important role in maintaining tubule structure. This led to chronic pancreatitis and formation of neoplasia through KRAS activation in mature acinar cells.…”
Section: Hnf1b Interactions and Target Genesmentioning
confidence: 97%
“…74 Inactivation of HNF1B by Cre-Sox9 recombination was found to cause chronic pancreatitis with dilation of ducts, acinar-to-ductal metaplasia and lipomatosis. 75 Inactivated HNF1B in mouse ductal cells was seen to decrease the expression of Prox1, Pkhd1, Spp1 and Cys1, which play an important role in maintaining tubule structure. This led to chronic pancreatitis and formation of neoplasia through KRAS activation in mature acinar cells.…”
Section: Hnf1b Interactions and Target Genesmentioning
confidence: 97%
“…In the exocrine pancreas, one regulatory module, containing NR5A2, was shared between acinar and ductal cells, although with a tendency for increased regulon activity in ductal cells (Figure 2D/H) . Other exocrine regulons included ONECUT1, REST and HNF1B with reported roles in exocrine development (Nissim et al , 2016; Kropp, Zhu and Gannon, 2019) and the adult exocrine pancreas (Quilichini et al , 2019; Bray et al , 2020) (Figure 2D) . In summary, this analysis confirms the expected separation of exocrine and endocrine cells with distinct gene regulatory programs, and identifies known and novel candidate regulators of pancreas cell states.…”
Section: Resultsmentioning
confidence: 93%
“…Top ranked regulons in ductal cells included well known regulators of ductal and exocrine cell identity such as POU2F3, NR5A2 and HNF1B (Nissim et al , 2016; Yamashita et al , 2017; Quilichini et al , 2019) (Figure 3E/F) . In addition, we observed CDX2 and PPARD as highly specific ductal regulons (Figure 3F/G) .…”
Section: Resultsmentioning
confidence: 99%
“…HNF1B is a member of the HNF family, participates in regulating the metabolism of lipids, carbohydrates and proteins, and plays an important role in regulating hepatocyte differentiation and liver development 20 . Recent studies have shown that HNF1B has a significant correlation with the occurrence and development of various tumors, such as prostate cancer and pancreatic cancer 21 , 22 . In this study, we found that the expression of HNF1B was upregulated at different levels in BLCA, CHOL, KIRP, LIHC, STAD, THCA, and UCEC and downregulated in COAD, GBM, KICH, KIRC, and LUSC.…”
Section: Discussionmentioning
confidence: 99%